Carbon nanotube water dispersion, carbon nanotube unwoven fabric, and methods of producing the same
By using cholic acid derivatives and basic compounds in the aqueous dispersion of carbon nanotubes, the problems of ionic liquid residues and high-temperature heat treatment oxidation in carbon nanotube nonwovens in the prior art are solved, and high-purity and high-performance carbon nanotube nonwovens are achieved.
Patent Information
- Application Number
- JP2023145602
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
In the production of high-purity carbon nanotube nonwoven fabrics, it is difficult to effectively remove residues in ionic liquids, and high-temperature heat treatment will lead to oxidation and degradation of carbon nanotubes, affecting purity and performance.
Using an aqueous carbon nanotube dispersion containing cholic acid derivatives and base compounds, the uniform dispersion of carbon nanotubes and the production of high-purity nonwoven fabrics are achieved through the pH adjustment of the basic solution and the selective dissolution of the cholic acid derivatives.
High purity production of carbon nanotube nonwoven fabrics is achieved, avoiding the problems of ionic liquid residues and carbon nanotube oxidation, and ensuring the excellent performance of nonwoven fabrics in mechanical and electrical properties.
Smart Images

Figure 2025038787000006 
Figure 2025038787000001 
Figure 2025038787000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous dispersion of carbon nanotubes, a nonwoven fabric of carbon nanotubes, and methods for producing the same. [Background technology]
[0002] It is known that nonwoven fabrics of carbon nanotubes can be produced directly from aggregates of carbon nanotubes produced in the gas phase; however, it is difficult from an equipment standpoint to directly turn the carbon nanotubes produced by a high-temperature reaction in the presence of hydrogen gas into nonwoven fabric, and the nonwoven fabric produced will have anisotropy in terms of strength (Patent Documents 1 to 4). Therefore, as a method for producing a nonwoven fabric of carbon nanotubes other than the gas phase method, a wet method using a dispersion liquid in which carbon nanotubes are dispersed in an organic solvent or an aqueous solution is known. In the wet method using a dispersion liquid of carbon nanotubes, a dispersant such as an ionic liquid or a surfactant is essential to uniformly disperse carbon nanotube aggregates in water or an organic solvent. For example, a carbon nanotube dispersion liquid using an organic acid sodium salt, an organic acid ammonium salt, or the like as a dispersant is described (Patent Document 5). Also known is a method of forming a sheet by filtering an aqueous dispersion containing fine cellulose fibers and carbon nanotubes (Patent Document 6). Also disclosed is a method for obtaining a carbon nanotube film from a carbon nanotube dispersion containing sodium deoxycholate as a dispersant (Patent Document 7). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-007304 A [Patent Document 2] JP 2013-241723 A [Patent Document 3] JP 2016-065350 A [Patent Document 4] JP 2016-102047 A [Patent Document 5] International Publication No. 2018 / 179760 [Patent Document 6] JP 2014-189932 A [Patent Document 7] JP 2015-178446 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, ionic liquids have problems with chemical stability, and the method described in Patent Document 7 has the problem of sodium ions remaining in the carbon nanotube film (carbon nanotube nonwoven fabric). A method of high-temperature heat treatment is considered for removing the dispersant from carbon nanotube nonwoven fabric produced by the wet method, but there is also the problem that the carbon nanotubes are oxidized and deteriorated by high-temperature heat treatment, making it difficult to reduce the amount of dispersant contained in the carbon nanotube nonwoven fabric and achieve high purity carbon nanotubes. Therefore, an object of the present invention is to provide an aqueous carbon nanotube dispersion suitable for producing a high-purity carbon nanotube nonwoven fabric and a method for producing the same. Another object of the present invention is to provide a high-purity carbon nanotube nonwoven fabric produced from the aqueous carbon nanotube dispersion and a method for producing the same. [Means for solving the problem]
[0005] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the following carbon nanotube aqueous dispersion can achieve the above object, thereby completing the present invention.
[0006] That is, the present invention provides the following carbon nanotube aqueous dispersion and the like. [1] For 100 parts by mass of water, Basic compound: 0.001 parts by mass or more; 0.001 parts by mass or more of a cholic acid derivative, and Carbon nanotubes: 0.01 to 10.0 parts by mass The carbon nanotube aqueous dispersion contains the cholic acid derivative in an amount of 0.1 to 5.0 (parts by mass / parts by mass) relative to the carbon nanotubes. [2] The carbon nanotube aqueous dispersion according to [1], wherein the cholic acid derivative is one or more selected from α-muricholic acid, β-muricholic acid, cholic acid, deoxycholic acid, ursodeoxycholic acid, hyodeoxycholic acid, chenodeoxycholic acid, dehydrocholic acid and lithocholic acid. [3] The carbon nanotube aqueous dispersion according to [1] or [2], wherein the basic compound is a nitrogen-containing compound. [4] The carbon nanotube aqueous dispersion according to [3], wherein the nitrogen-containing compound is ammonia. [5] The carbon nanotube aqueous dispersion was measured at a shear rate of 100 s at 25° C. using a cone-plate type rotational viscometer described in JIS K7117-2:1999. -1 Viscosity (η100) and shear rate at 0.1s -1 The carbon nanotube aqueous dispersion according to any one of [1] to [4], having a thixotropy ratio, which is the ratio (η0.1 / η100) of the viscosity at η0.1 to the viscosity at η0.1, of 50 to 1,000. [6] A step of preparing an aqueous dispersion solution containing 100 parts by mass of water, 0.001 parts by mass or more of a basic compound, and 0.001 parts by mass or more of a cholic acid derivative. and A step of dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass). The present invention relates to a method for producing an aqueous dispersion of carbon nanotubes. [7] (1) adding and mixing 0.001 parts by mass or more of a basic compound into 100 parts by mass of water to prepare a basic aqueous solution having a pH of 8 to 12; (2) dissolving 0.001 parts by mass or more of a cholic acid derivative in the basic aqueous solution to prepare an aqueous solution for dispersion; and (3) dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass); The present invention relates to a method for producing an aqueous dispersion of carbon nanotubes. [8] (4) A process for producing a carbon nanotube thin film by applying the carbon nanotube aqueous dispersion according to any one of items (1) to (5) on a support to a thickness of 5 mm or less and removing water in a drying furnace; and (5) peeling the carbon nanotube thin film obtained in step (4) from the support; At atmospheric pressure, at temperatures between 250℃ and 500℃ or At temperatures between 150°C and 500°C under subatmospheric pressure Heat treatment process A method for producing a carbon nanotube nonwoven fabric comprising the steps of: A method for producing a carbon nanotube nonwoven fabric, in which a residual amount of a cholic acid derivative in the carbon nanotube nonwoven fabric is 0 mass % or more and less than 10 mass %. [9] The method for producing a carbon nanotube nonwoven fabric according to [8], wherein the heat treatment is carried out in an inert gas.
[10] A carbon nanotube nonwoven fabric having a sodium atom content of 1.0 mass % or less.
[11] The carbon nanotube nonwoven fabric according to
[10] , having a tensile strength ratio in the longitudinal direction to the transverse direction (tensile strength in the longitudinal direction / tensile strength in the transverse direction) of 0.95 to 1.05. Effect of the Invention
[0007] The carbon nanotube aqueous dispersion of the present invention has excellent coatability and is particularly suitable for producing a high-purity carbon nanotube nonwoven fabric because the cholic acid derivative contained as a dispersant is removed within a temperature range in which the carbon nanotubes are not oxidized and deteriorated. Moreover, the carbon nanotube aqueous dispersion of the present invention makes it possible to produce a carbon nanotube nonwoven fabric that is free of anisotropy in terms of strength using a relatively simple device. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a schematic diagram showing a measurement system for transmission loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will now be described in more detail.
[0010] [Carbon nanotube water dispersion] The carbon nanotube aqueous dispersion of the present invention is a dispersion of carbon nanotubes in water containing a cholic acid derivative and a basic compound. Each component contained in the carbon nanotube aqueous dispersion of the present invention will be described below.
[0011] Carbon Nanotubes The carbon nanotubes may be single-walled or multi-walled carbon nanotubes, or may be a mixture of these. The method for producing the carbon nanotubes is not particularly limited, and those produced by known methods or commercially available ones may be used. The shape of the carbon nanotubes is also not particularly limited, but when used in the production of the carbon nanotube nonwoven fabric described below, it is preferable that the diameter of the carbon nanotubes is 50 nm or less and the length of the carbon nanotubes is 2 mm or less in terms of the strength of the nonwoven fabric.
[0012] The amount of carbon nanotubes blended in the aqueous dispersion is 0.01 to 10.0 parts by mass, preferably 0.05 to 5.0 parts by mass, and more preferably 0.1 to 2.5 parts by mass, per 100 parts by mass of water.
[0013] Cholic Acid Derivatives The present invention is characterized by using a cholic acid derivative as a dispersant. In the present invention, the cholic acid derivative is a general term for cholic acid and compounds that differ from cholic acid in the presence or absence of a substituent and / or the steric position of the substituent. In the present invention, the cholic acid derivative does not include salts of cholic acid derivatives such as sodium cholate. Examples of cholic acid derivatives include α-muricholic acid, β-muricholic acid, cholic acid, deoxycholic acid, ursodeoxycholic acid, hyodeoxycholic acid, chenodeoxycholic acid, dehydrocholic acid, and lithocholic acid, etc. Among these, deoxycholic acid is preferred.
[0014] The amount of the cholic acid derivative to be blended is 0.001 parts by mass or more relative to 100 parts by mass of water, and the upper limit can be optimized depending on the amount of carbon nanotubes in the dispersion liquid. The compounding ratio (mass ratio) of the carbon nanotubes to the cholic acid derivative may be 0.10 to 5.0, preferably 0.20 to 3.0, and more preferably 0.50 to 2.0, of the cholic acid derivative to the carbon nanotubes.
[0015] Basic Compounds As the basic compound, a nitrogen-containing compound is preferred, and among the nitrogen-containing compounds, a nitrogen-containing compound that is water-soluble and has a boiling point of preferably 200° C. or less, more preferably 150° C. or less, is more preferred. More specific examples of the basic compound include organic amine derivatives and ammonia. As the organic amine derivative, any organic amine that dissolves in water can be used. Examples of the organic amine derivative include low molecular weight amine compounds such as monomethylamine, dimethylamine, trimethylamine, and ethylenediamine. Among them, ammonia is preferred as the basic compound.
[0016] The amount of the basic compound added is 0.001 part by mass or more relative to 100 parts by mass of water. The upper limit of the amount of the basic compound added is not particularly limited as long as the pH of the aqueous solution at 25° C. is within the range of 8 to 12.
[0017] [Method of manufacturing carbon nanotube aqueous dispersion] The carbon nanotube aqueous dispersion of the present invention can be produced by dispersing carbon nanotubes in water containing a cholic acid derivative and a basic compound. In this specification, the mixture of water, the cholic acid derivative, and the basic compound is also referred to as an "aqueous dispersion solution." The aqueous dispersion solution may be prepared by adding the cholic acid derivative and the basic compound to water at the same time and mixing, or may be added separately and mixed. The carbon nanotube aqueous dispersion of the present invention can be prepared, for example, by the following steps: A step of preparing an aqueous dispersion solution containing 100 parts by mass of water, 0.001 parts by mass or more of a basic compound, and 0.001 parts by mass or more of a cholic acid derivative. and A step of dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass). The composition can be produced by a method comprising the steps of: The carbon nanotube aqueous dispersion of the present invention can be preferably produced, for example, by a method including the following steps (1) to (3). (1) A step of adding and mixing 0.001 parts by mass or more of a basic compound to 100 parts by mass of water to prepare a basic aqueous solution having a pH of 8 to 12. (2) A step of dissolving 0.001 parts by mass or more of a cholic acid derivative in the basic aqueous solution to prepare an aqueous solution for dispersion. (3) A step of dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass) The carbon nanotube aqueous dispersion of the present invention may be produced by preparing an aqueous dispersion solution according to the following steps (1') to (2') instead of the above steps (1) to (2), and then carrying out the above step (3). (1') A step of adding and mixing 0.001 parts by mass or more of a cholic acid derivative into 100 parts by mass of water to prepare a cholic acid derivative dispersion liquid (2') A step of adding and mixing 0.001 parts by mass or more of a basic compound to the cholic acid derivative dispersion liquid to prepare an aqueous dispersion solution having a pH of 8 to 12. In the present invention, it has been found that by using a basic aqueous solution with a pH of 8 to 12, preferably pH 8.5 to 11.5, as a dispersion medium for carbon nanotubes, a cholic acid derivative that is poorly soluble in water exists in a dissolved state in the carbon nanotube aqueous dispersion and acts as a dispersant for carbon nanotubes. Since the cholic acid derivative can be dissolved in any ratio if the solution is basic, specifically, if the solution has a pH of 8 or more, the amount of cholic acid derivative to be added can be freely selected depending on the amount of carbon nanotubes in the dispersion.
[0018] In the step (1) of preparing a basic aqueous solution, 0.001 parts by mass or more of a basic compound is added to 100 parts by mass of water and mixed to obtain a basic aqueous solution having a pH of 8 to 12. The pH of the basic aqueous solution is a value at 25°C. The upper limit of the amount of the basic compound added may be within a range in which the pH of the aqueous solution is 8 to 12, and is appropriately determined depending on the type of the basic compound. For example, when ammonia is used as the basic compound, the amount of ammonia added to 100 parts by mass of water is 0.001 to 28 parts by mass, preferably 0.01 to 5 parts by mass. In addition, when a low molecular weight amine compound is used as the basic compound, the amount of the low molecular weight amine compound added to 100 parts by mass of water is 0.001 to 10 parts by mass, preferably 0.01 to 5 parts by mass.
[0019] In the step (2) of preparing an aqueous solution for dispersion, 0.001 parts by mass or more of a cholic acid derivative is added to the basic aqueous solution prepared in the step (1) and dissolved to prepare an aqueous solution for dispersion. In the step (2), various stirring devices may be used to dissolve the cholic acid derivative.
[0020] In the step (1') of preparing a cholic acid derivative dispersion, 0.001 parts by mass or more of a cholic acid derivative is added to 100 parts by mass of water and mixed. In the step (1'), the cholic acid derivative is present in a dispersed state in water.
[0021] In the step (2') of preparing an aqueous dispersion solution, 0.001 parts by mass or more of a basic compound is added to and mixed with the cholic acid derivative dispersion liquid prepared in the above step (1') to obtain an aqueous dispersion solution having a pH of 8 to 12. The pH of the aqueous dispersion solution is measured at 25°C. The upper limit of the amount of the basic compound to be added may be an amount that dissolves the cholic acid derivative within a pH range of 8 to 12 of the aqueous dispersion solution, and is appropriately determined depending on the type of basic compound, but is specifically as described in the above step (1). In the step (2'), various stirring devices may be used to dissolve the cholic acid derivative.
[0022] In the step (3) of dispersing carbon nanotubes, 0.01 to 10.0 parts by mass of carbon nanotubes and an amount of cholic acid derivative added relative to the carbon nanotubes of 0.1 to 5.0 (parts by mass / parts by mass) are added to the aqueous dispersion prepared in step (2) or (2') and dispersed to prepare an aqueous dispersion of carbon nanotubes. The apparatus used for the dispersion treatment may be a conventionally known one. In some cases, dispersion treatment using ultrasonic waves, dispersion treatment using a jet mill, dispersion treatment using high shear stirring, etc. may be used, but it is preferable to use such a method within a range that does not impair the properties of the carbon nanotubes or microfibers. Only one method of distributed processing may be adopted, or a plurality of distributed processing methods may be combined.
[0023] Generally, when applying a liquid material with a coater, it is desirable to use a highly thixotropic material that has the properties of low viscosity in the high shear region and high viscosity in the low shear region as the liquid resin characteristics. Therefore, in the case of producing a carbon nanotube nonwoven fabric in the present invention, the carbon nanotube aqueous dispersion preferably has a thixotropy ratio of 50 to 1,000, more preferably 100 to 1,000. In the present invention, the thixotropy ratio is the ratio of the shear rate of 100 s 2 measured at 25° C. by a cone-plate type rotational viscometer described in JIS K7117-2:1999. -1 Viscosity (η100) and shear rate at 0.1s -1 This refers to the ratio (η0.1 / η100) of the viscosity (η0.1) at If the thixotropy ratio of the carbon nanotube aqueous dispersion is 50 to 1,000, when the carbon nanotube aqueous dispersion is applied to a support, the shape at the time of application is easily maintained, there is little difference in thickness between the center and ends of the application, and a uniform film can be obtained, which is preferable. In addition, the shear rate is 100 s -1 The viscosity (η100) at the shear rate of 0.1 s is preferably 0.1 to 5 Pa s, and more preferably 0.2 to 2.5 Pa s. -1 The viscosity (η0.1) is 10~5×10 3 Pa·s is preferable, and 50 to 1,000 Pa·s is more preferable. The viscosity and thixotropy of the dispersion are determined by the mixing ratio of water and carbon nanotubes, the type and amount of dispersant, etc.
[0024] [Carbon nanotube nonwoven fabric and its manufacturing method] The carbon nanotube aqueous dispersion of the present invention can be suitably used for producing a carbon nanotube nonwoven fabric, which can be produced, for example, by a method including the following steps (4) and (5). (4) A step of coating the carbon nanotube aqueous dispersion of the present invention, preferably the carbon nanotube aqueous dispersion obtained by the above steps (1) to (3), on a support to a thickness of 5 mm or less, and removing water in a drying furnace to produce a carbon nanotube thin film. (5) peeling the carbon nanotube thin film obtained in step (4) from the support, and heat-treating it at a temperature of 250° C. to 500° C. under atmospheric pressure or at a temperature of 150° C. to 500° C. under a pressure less than atmospheric pressure to remove the cholic acid derivative.
[0025] In order to form a thin film from the aqueous dispersion without repelling, the surface of the support preferably has a contact angle with water of 120° or less, more preferably 110° or less and 70° or more. The shape of the support is not particularly limited to a film or plate, but in the case of a film, the material is preferably a thermoplastic or thermosetting resin with a softening temperature of 50° C. or more. In the case of a plate, the material is not particularly limited as long as it is a material that does not deform at the temperature at which water is dried, such as SUS, aluminum, FRP, etc., but a material with excellent releasability, whose surface is coated with fluororesin, etc., is preferable. In the case of a contact angle with water exceeding 120° or the material of the support has low wettability, a support whose surface has been treated with plasma, UV, etc. may be used. Examples of the support include films of polypropylene, polyethylene terephthalate, polyimide, polyethylene, fluororesin, and the like.
[0026] As a coating device for coating the carbon nanotube aqueous dispersion on the support in step (4), a roll coater, gravure coater, reverse coater, slot die coater, leap coater, bladed roll coater, blade coater, etc. can be used. Among them, a slot die coater or blade coater capable of coating a thick film is preferred.
[0027] In step (4), the carbon nanotube aqueous dispersion of the present invention is applied onto a support using the above-mentioned film-forming coating device to form a carbon nanotube thin film of a predetermined thickness. For example, when a slot die coater is used, the dispersion is extruded onto the support with a slot die to a predetermined thickness to form a thin film. The heating temperature and residence time in the drying oven are optional as long as the moisture can be removed, but usually the moisture can be sufficiently removed at 50°C to 150°C for 30 minutes to 10 hours. The coating thickness of the dispersion on the support is 5 mm or less, preferably 10 μm to 5 mm, depending on the amount of carbon nanotubes mixed in. When the carbon nanotube aqueous dispersion coated to a coating thickness of 10 μm to 5 mm is passed through a drying furnace as described above to remove water, a carbon nanotube thin film having a thickness of 0.01 μm to 1 mm is obtained. In order to adjust the thickness of the carbon nanotube thin film to be more uniform, the thickness may be adjusted using a pressure roll or the like after removing moisture.
[0028] The carbon nanotube thin film obtained in step (4) may contain cholic acid derivatives and basic compounds. Therefore, in order to remove the cholic acid derivatives and basic compounds contained in the carbon nanotube thin film, in step (5), the carbon nanotube thin film is peeled off from the support and heat-treated at a predetermined temperature.
[0029] In the heat treatment in step (5), the carbon nanotube thin film peeled off from the support may be directly placed in a heat treatment furnace, but a method is preferred in which the carbon nanotube thin film peeled off from the support is wound up on a cylinder and the cylinder is placed in a heat treatment furnace for heating. The cylinder may be made of metal or ceramics such as glass. In order to perform the heat treatment uniformly, a cylinder having through holes, preferably multiple and of any shape, on the side wall of the cylinder is preferred.
[0030] The heat treatment is performed at a temperature of 250°C to 500°C under atmospheric pressure or at a temperature of 150°C to 500°C under a pressure less than atmospheric pressure. Heat treatment at a temperature higher than 500°C is not preferable because it causes oxidation and deterioration of the carbon nanotubes. The lower limit of the heat treatment temperature is the temperature at which the cholic acid derivative and the basic compound are removed, and is 250°C or higher under atmospheric pressure from the viewpoint of productivity, and is 150°C or higher under a pressure less than atmospheric pressure, i.e., when the pressure in the heat treatment system is reduced to less than 1 atmosphere (1013 hPa). The heat treatment temperature under atmospheric pressure is more preferably 250°C to 450°C, and even more preferably 300°C to 400°C. The heat treatment may be performed in an atmosphere containing oxygen such as air, but is preferably performed in an inert gas atmosphere such as nitrogen to suppress oxidation of the carbon nanotubes. In particular, it is more preferable to perform the heat treatment under an atmospheric pressure less than atmospheric pressure. Since carbon nanotubes are gradually oxidized at 400°C or higher, the heat treatment may be performed in an air atmosphere when the heat treatment is performed at less than 400°C for a short period of time, but is preferably performed in an inert gas atmosphere when the heat treatment temperature is 400°C or higher or when the heat treatment is performed for a relatively long period of time. The heat treatment time depends on the heat treatment temperature, but is, for example, 0.5 to 50 hours, preferably 2 to 40 hours, and particularly 0.5 to 20 hours under an atmospheric pressure lower than atmospheric pressure.
[0031] After the heat treatment, the carbon nanotube nonwoven fabric is removed from the heat treatment furnace to obtain a sheet-like carbon nanotube nonwoven fabric. If the carbon nanotube thin film wound around the cylinder is subjected to the heat treatment together with the cylinder, the thin film may be unwound and cut into a sheet. The carbon nanotube nonwoven fabric obtained may be used in sheet form, or may be wound around a paper cylinder to obtain a roll. In addition, a plurality of the carbon nanotube nonwoven fabrics obtained may be stacked and laminated under pressure to obtain a nonwoven fabric of a desired thickness. The method of the present invention makes it possible to easily and productively produce continuous nonwoven fabric having a width of 10 cm to 150 cm and a length of 1 m or more, or sheets cut to a fixed length.
[0032] The carbon nanotube nonwoven fabric of the present invention may be surface-treated with silanes (silane coupling agents) or metal alkoxides. In this case, the surface treatment can be easily performed after step (5) by subjecting the fabric to a heat treatment in an aqueous solution containing silane or an organic solvent containing polysilazane. A preferred silane coupling agent is, for example, a compound represented by the general formula Y-Si-X3, where Y is an organic group having a functional group such as an amino group, an epoxy group, a hydroxyl group, a carboxyl group, a vinyl group, a methacryl group, or a mercapto group, and X is a hydrolyzable functional group such as an alkoxy group. Representative examples of the compound represented by the general formula Y-Si-X3 include γ-glycidoxypropyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-aminobenzyltriethoxysilane, and γ-aminophenyltriethoxysilane. As the silane coupling agent used as the surface treatment agent for the carbon nanotube nonwoven fabric, aminosilanes are preferred.
[0033] The carbon nanotube nonwoven fabric produced in this way is safe and easy to handle, as the nano-sized carbon nanotubes do not scatter. Furthermore, when the carbon nanotubes are impregnated with a resin to produce a composite material, the adhesion to the resin is improved, resulting in improved breaking strength and toughness.
[0034] The content of the cholic acid derivative in the carbon nanotube nonwoven fabric obtained by the production method of the present invention is from 0% by mass to less than 10% by mass, preferably 0.1% by mass or less, and more preferably 0.01% by mass or less. The content (residual amount) of the cholic acid derivative in the carbon nanotube nonwoven fabric can be calculated based on the weight change before and after measurement of the carbon nanotube thin film obtained in step (4) using a simultaneous differential thermal and thermogravimetric analyzer set under the same heat treatment conditions as in step (5).
[0035] The content of sodium atoms in the carbon nanotube nonwoven fabric obtained by the production method of the present invention is preferably 1.0 mass% or less. The content of sodium atoms in the carbon nanotube nonwoven fabric can be quantified by energy dispersive X-ray spectroscopy.
[0036] The carbon nanotube nonwoven fabric preferably has a longitudinal to transverse tensile strength ratio of 0.95 to 1.05, more preferably 0.97 to 1.03. When the ratio is within this range, the composite material will have high strength, high toughness, and high impact strength. The tensile strength was measured by cutting a 10mm x 100mm test piece from the nonwoven fabric and measuring it using a tensile testing machine under conditions of a gripping width of 50mm and a tensile speed of 100mm / min. The longitudinal tensile strength was measured on a test piece obtained by cutting the carbon nanotube nonwoven fabric in the longitudinal direction, and the transverse tensile strength was measured on a test piece obtained by cutting the carbon nanotube nonwoven fabric in the transverse direction. In the present invention, the ratio of tensile strength in the longitudinal direction to the transverse direction is a value calculated from the average value of three measurements of the tensile strength in the longitudinal direction and the transverse direction, as the ratio of the tensile strength in the longitudinal direction to the tensile strength in the transverse direction. The vertical direction is the coating direction when the carbon nanotube aqueous dispersion is applied in the step (4), and the horizontal direction is the width direction (direction perpendicular to the coating direction) when the carbon nanotube aqueous dispersion is applied in the step (4).
[0037] [Composite materials] The carbon nanotube nonwoven fabric of the present invention may be impregnated with a resin to form a composite material. Resin binders used in composite materials include thermosetting resins and thermoplastic resins. For example, thermosetting resins include epoxy resins, phenolic resins, silicone resins, maleimide resins, polyimide resins, and bismaleimide resins. Thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polyester, and fluororesins. Furthermore, the carbon nanotube nonwoven fabric of the present invention may be laminated with carbon fiber cloth and / or glass cloth, and then combined with the resin to form a composite material, which has high strength, high toughness, and high impact resistance. The carbon nanotube nonwoven fabric of the present invention has excellent electrical conductivity and therefore exhibits excellent performance as an electromagnetic wave shielding material in a wide frequency range from a few hertz to the gigahertz band. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass". The materials used in the examples and comparative examples are shown below. The physical properties and characteristic values in the present invention were measured by the following methods.
[0039] <Carbon nanotubes> (1) Single-walled carbon nanotube; Meijo Nano Carbon Co., Ltd. EC1.5-P (2) Multi-walled carbon nanotubes; Meijo Nano Carbon Co., Ltd. EC2.0-P <Basic compounds> (1) 1mol / L ammonia water; Fuji stomach Manufactured by Wako Pure Chemical Industries, Ltd. (2) Ethylenediamine; Fujif stomach Manufactured by Wako Pure Chemical Industries, Ltd. <Cholic acid derivatives> (1) Cholic acid; Fujif stomach Manufactured by Wako Pure Chemical Industries, Ltd. (2) Deoxycholic acid; Fujif stomach Manufactured by Wako Pure Chemical Industries, Ltd. (3) Ursodeoxycholic acid; Fujifilm stomach Manufactured by Wako Pure Chemical Industries, Ltd. (4) Chenodeoxycholic acid; Fujifilm stomach Manufactured by Wako Pure Chemical Industries, Ltd. (5) Sodium deoxycholate; Fujif stomach Manufactured by Wako Pure Chemical Industries, Ltd.
[0040] 1. How to measure pH: The liquid to be measured was left to stand in a thermostatic bath at 25°C for 1 hour, and then the pH was measured using a pH meter (PHD-210P, manufactured by Horiba, Ltd.).
[0041] 2.Method of measuring thixotropy: Carbon nanotube water dispersion at a shear rate of 100 s -1 Viscosity (η100) and shear rate 0.1s -1 The viscosity (η0.1) of each was measured, and η0.1 / η100 was taken as the thixotropic ratio. The viscosity was measured at 25°C using a Brookfield DV-III ULTRA with a φ48 mm parallel cone (500 μm).
[0042] 3. Method for measuring remaining amount of cholic acid derivatives: The carbon nanotube thin film obtained in step (4) of each Example was peeled off from the support, and the amount of the cholic acid derivative remaining was determined from the change in weight before and after the heat treatment. The weight ratio of carbon nanotubes to cholic acid derivatives in the carbon nanotube thin film was assumed to be the same as the weight ratio of carbon nanotubes to cholic acid derivatives in the carbon nanotube aqueous dispersion, and the remaining amount of cholic acid derivatives was estimated from the weight loss before and after heat treatment.
[0043] 4.Method of measuring tensile strength ratio: The tensile strength of the nonwoven fabric was measured by cutting a test piece of 10 mm x 100 mm from the nonwoven fabric and measuring it with an autograph (AGS-500NS) manufactured by Shimadzu Corporation under the conditions of a gripping width of 50 mm and a pulling speed of 100 mm / min. The tensile strength in the longitudinal and transverse directions was measured by cutting test pieces in the longitudinal and transverse directions, with the coating direction of the produced nonwoven fabric being the longitudinal direction and the width direction being the transverse direction. The tensile strength ratio was calculated by averaging the test results of measurements taken three times in each of the longitudinal and transverse directions, and calculating the ratio of the longitudinal tensile strength to the transverse tensile strength.
[0044] 5.Method of measuring resistivity: The resistivity was calculated using the following formula. Specific resistance (Ω cm) = surface resistivity (Ω / sq.) x thickness (cm) The surface resistivity was measured using a Loresta-GX MCP-T700 (a low-resistance resistivity meter manufactured by Nitto Seiko Analytech Co., Ltd.) and the measured value was used to calculate the specific resistance.
[0045] 6. Transmission loss measurement method: A schematic diagram of the transmission loss measurement system is shown in Figure 1. Carbon nanotube nonwoven fabric or composite material was used as the measurement sample, and the transmission loss at 70 GHz was measured using an electromagnetic shielding measurement device manufactured by Keycom. For electromagnetic waves with an electric field vibration in the y-axis direction, the "longitudinal transmission loss" was measured by placing the measurement sample so that the longitudinal direction of the measurement sample was parallel to the y-axis, and the "lateral transmission loss" was measured by placing the measurement sample so that the longitudinal direction of the measurement sample was perpendicular to the y-axis, and the longitudinal / lateral transmission loss ratio was calculated.
[0046] Example 1 2.5 parts by mass of ammonia water with an ammonia concentration of 1 mol / L was mixed with 100 parts by mass of water to prepare a basic aqueous solution with a pH of 10. 0.4 parts by mass of cholic acid was added as a dispersant to a beaker containing the basic aqueous solution, and the mixture was stirred with a mixer (manufactured by Iwatani Corporation, IFM-800DGM) until the cholic acid was completely dissolved, to obtain an aqueous solution for dispersion. 0.4 parts by mass of single-walled carbon nanotubes were added to the aqueous solution for dispersion, and the mixture was mixed with a mixer rotating at 20,000 rpm for 1 minute to produce an aqueous dispersion of carbon nanotubes. The viscosity of the carbon nanotube aqueous dispersion is at a shear rate of 0.1 s -1 The viscosity under low shear conditions is 237 Pa s, and the shear rate is 100 s -1 Under high shear conditions, the value was 0.27 Pa s.
[0047] Examples 2 to 12 Eleven types of carbon nanotube aqueous dispersions were produced by mixing each component in a mixer in accordance with the method described in Example 1, except that the basic aqueous solution, cholic acid derivative, and carbon nanotubes were used in the proportions shown in Table 1. Example 13 0.4 parts by mass of deoxycholic acid was mixed with 100 parts by mass of water as a dispersant to prepare a deoxycholic acid dispersion. 2.5 parts by mass of ammonia water with an ammonia concentration of 1 mol / L was added to the deoxycholic acid dispersion, and the mixture was stirred with a mixer (manufactured by Iwatani Corporation, IFM-800DGM) until the deoxycholic acid was completely dissolved to obtain an aqueous dispersion solution. 0.4 parts by mass of single-walled carbon nanotubes were added to the aqueous dispersion solution, and the mixture was mixed with a mixer rotating at 20,000 rpm for 1 minute to produce an aqueous carbon nanotube dispersion solution. The pH of the basic aqueous solution or the aqueous dispersion solution of each Example and the shear viscosity of the carbon nanotube aqueous dispersion were measured by the above-mentioned method, and the thixotropy ratio was calculated from the shear viscosity measurement results. These results are shown in Table 1.
[0048] [Table 1]
[0049] Comparative Example 1 When 0.4 parts by mass of deoxycholic acid was added as a dispersant to a beaker containing 100 parts by mass of ammonia-free water of pH 7 instead of the basic aqueous solution of Example 2 and stirred, the deoxycholic acid did not completely dissolve. 0.4 parts by mass of single-walled carbon nanotubes were added to this aqueous dispersion solution and mixed for 1 minute with a mixer rotating at 20,000 rpm to produce an aqueous dispersion of carbon nanotubes. It was confirmed that the carbon nanotubes in the carbon nanotube aqueous dispersion maintained aggregates of a visible size, and thus the dispersibility was insufficient.
[0050] Comparative Example 2 0.4 parts by mass of sodium deoxycholate was added as a dispersant to a beaker containing 100 parts by mass of ammonia-free water with a pH of 7, and the mixture was stirred until the sodium deoxycholate was completely dissolved. 0.4 parts by mass of single-walled carbon nanotubes were added to this aqueous dispersion solution, and the mixture was mixed for 1 minute with a mixer rotating at 20,000 rpm to produce an aqueous dispersion of carbon nanotubes. The viscosity of the carbon nanotube aqueous dispersion is at a shear rate of 0.1 s-1 The viscosity under low shear conditions is 122 Pa s, and the shear rate is 100 s -1 Under high shear conditions, the value was 0.27 Pa s.
[0051] Comparative Example 3 A basic aqueous solution with a pH of 9 was prepared by mixing 1.0 part by mass of ammonia water with an ammonia concentration of 1 mol / L with 100 parts by mass of water. 0.02 parts by mass of deoxycholic acid was added as a dispersant to a beaker containing the basic aqueous solution, and the mixture was stirred with a mixer (manufactured by Iwatani Corporation, IFM-800DGM) until the deoxycholic acid was completely dissolved, to obtain an aqueous solution for dispersion. 0.4 parts by mass of single-walled carbon nanotubes were added to the aqueous solution for dispersion, and the mixture was mixed for 1 minute with a mixer rotating at 20,000 rpm to produce an aqueous dispersion of carbon nanotubes. It was confirmed that the carbon nanotubes in the carbon nanotube aqueous dispersion maintained aggregates of a visible size, and thus the dispersibility was insufficient.
[0052] Comparative Example 4 8.0 parts by mass of ammonia water with an ammonia concentration of 1 mol / L was mixed with 100 parts by mass of water to prepare a basic aqueous solution with a pH of 11. 1.0 part by mass of deoxycholic acid was added as a dispersant to a beaker containing the basic aqueous solution, and the mixture was stirred with a mixer (manufactured by Iwatani Corporation, IFM-800DGM) until the deoxycholic acid was completely dissolved, to obtain an aqueous dispersion. 0.4 parts by mass of single-walled carbon nanotubes were added to this aqueous dispersion, and the mixture was mixed for 1 minute with a mixer rotating at 20,000 rpm to produce an aqueous dispersion of carbon nanotubes. The viscosity of the carbon nanotube aqueous dispersion is at a shear rate of 0.1 s -1 The viscosity under low shear conditions is 4.95 Pa s, and the shear rate is 100 s -1 Under high shear conditions, the value was 0.11 Pa s.
[0053] Comparative Example 5 In the same manner as in Example 1, 0.4 parts by mass of deoxycholic acid was added as a dispersant to a beaker containing the basic aqueous solution of pH 10 of Example 1, and the mixture was stirred until the deoxycholic acid was completely dissolved to obtain an aqueous dispersion solution. 12 parts by mass of multi-walled carbon nanotubes were added to this aqueous dispersion solution, and the mixture was mixed for 1 minute with a mixer rotating at 20,000 rpm to produce an aqueous dispersion solution of carbon nanotubes. The viscosity of the carbon nanotube dispersion solution is at a shear rate of 0.1 s -1 The viscosity under low shear conditions is 2780 Pa s, and the shear rate is 100 s -1 Under high shear conditions, the value was 2.6 Pa s.
[0054] The pH of the basic aqueous solution or dispersion medium and the shear viscosity of the carbon nanotube aqueous dispersion of each comparative example were measured by the above-mentioned method, and the thixotropy ratio was calculated from the shear viscosity measurement results. These results are shown in Table 2.
[0055] [Table 2]
[0056] Next, a carbon nanotube nonwoven fabric was produced by a wet method using the carbon nanotube aqueous dispersion prepared in the above example.
[0057] Example 14 The carbon nanotube aqueous dispersion produced in Example 1 was coated on a fluororesin film support (manufactured by AGC, product name: Aflex) with a thickness of 1 mm, a coating width of 28 cm, and a length of 30 m using a die coater (manufactured by ERS). This coated product was dried by moving it at 20 cm / min in a drying furnace heated to 150°C. The dried carbon nanotube thin film on the fluororesin film was peeled off from the fluororesin film and wound up to a thickness of 3 mm on a cylinder (made of iron, outer diameter 100 mm, thickness 10 mm, with multiple through holes in the side wall, hereafter referred to as "iron pipe") This iron pipe was placed in a heating furnace heated to 300°C in a nitrogen atmosphere, and heated for 14 hours while flowing nitrogen to produce a carbon nanotube nonwoven fabric (1) from which cholic acid, ammonia, etc. had been removed.
[0058] Examples 15 to 19 The carbon nanotube aqueous dispersions produced in Examples 2, 4, 7, 10, and 12 were used and subjected to coating, drying, and heat treatment under the same conditions as in Example 14 to produce nonwoven fabrics (2 to 6).
[0059] Examples 20 to 21 Carbon nanotube nonwoven fabrics (7 to 8) were produced in the same manner as in Example 15, except that the heat treatment conditions were as shown in Table 3. The physical properties of the carbon nanotubes of each example were measured by the above-mentioned methods. The results are shown in Table 3.
[0060] [Table 3]
[0061] Comparative Example 6 A carbon nanotube nonwoven fabric (9) was produced in the same manner as in Example 15, except that the heat treatment conditions were as shown in Table 4.
[0062] Comparative Example 7 A carbon nanotube nonwoven fabric (10) was produced in the same manner as in Example 15, except that the heat treatment conditions were as shown in Table 4.
[0063] Comparative Example 8 A carbon nanotube nonwoven fabric (11) was produced in the same manner as in Example 15, except that the heat treatment conditions were as shown in Table 4. As a result of TG, a weight loss was confirmed that was greater than the content of the cholic acid derivative, suggesting that a portion of the carbon nanotubes had been oxidized and deteriorated. The physical properties of the carbon nanotubes of each comparative example were measured by the above-mentioned methods. The results are shown in Table 4.
[0064] [Table 4]
[0065] Using the carbon nanotube aqueous dispersions prepared in Comparative Examples 1 to 5, an attempt was made to manufacture a carbon nanotube nonwoven fabric by a wet method. However, the carbon nanotube aqueous dispersions 14, 16, and 18 of Comparative Examples 1, 3, and 5 had low dispersibility of carbon nanotubes, and when these were applied to a support, problems occurred such as the inability to form a uniform carbon nanotube thin film and the occurrence of tears when peeled off from the support. In addition, since the carbon nanotube aqueous dispersion 15 of Comparative Example 2 contains sodium atoms, even if a nonwoven fabric is manufactured from it, the presence of sodium atoms in the nonwoven fabric may cause problems such as the nonwoven fabric becoming hydrophilic, and the resin deteriorating when it is made into a composite material. Note that, using the carbon nanotube aqueous dispersion 15 of Comparative Example 2, coating, drying, and heat treatment were performed under the same conditions as in Example 14 to manufacture a nonwoven fabric, and the content of sodium atoms in the nonwoven fabric was quantified by energy dispersive X-ray spectroscopy to be 8.3 mass%. Furthermore, the carbon nanotube aqueous dispersion 17 of Comparative Example 4 had a large amount of cholic acid derivative relative to the carbon nanotubes and was poor in thixotropy, so that a uniform carbon nanotube thin film could not be formed on the support, and as a result, a carbon nanotube nonwoven fabric with a uniform thickness could not be produced. Also, the carbon nanotube aqueous dispersion had a large content of cholic acid derivative, so that the heating temperature and heating time in the heat treatment step for removing it had to be increased and / or prolonged, which is undesirable since it may cause oxidative deterioration of the carbon nanotubes.
[0066] Next, various composite materials were produced using the carbon nanotube nonwoven fabric produced in Example 14.
[0067] Application example 1 A toluene solution containing 100 parts by mass of a bismaleimide resin (A-1) (SLK-3000, manufactured by Shin-Etsu Chemical Co., Ltd.), 1 part by mass of a curing catalyst (dicumyl peroxide (product name: "Percumyl D"), manufactured by NOF Corporation), and 200 parts by mass of toluene was prepared. The carbon nanotube nonwoven fabric produced in Example 14 was impregnated with this toluene solution, and the toluene was then dried and removed to produce a nonwoven fabric impregnated with the semi-cured bismaleimide resin. The nonwoven fabric was pressurized and cured for 30 minutes at 150° C. to produce a resin-impregnated nonwoven fabric sheet having a thickness of 65 μm. The transmission loss in the machine direction and the cross direction was measured using this sheet. In addition, test pieces were cut out from the machine direction and the cross direction of the nonwoven fabric sheet to measure the tensile strength. The measurement results are shown in Table 5.
[0068] Application example 2 A sheet of carbon fiber prepreg (TR3110; manufactured by Mitsubishi Chemical Corporation) was placed on each side of the bismaleimide resin-impregnated nonwoven fabric prepreg produced in Application Example 1, laminated into three layers, and heat-cured in a press at 200°C for 30 minutes to obtain a three-layer carbon nanotube nonwoven fabric composite sheet. The transmission loss in the machine direction and the cross direction was measured using this sheet. In addition, test pieces were cut out from the machine direction and the cross direction of the nonwoven fabric sheet to measure the tensile strength. The measurement results are shown in Table 5.
[0069] Application example 3 On both sides of the bismaleimide resin-impregnated nonwoven fabric prepreg produced in Application Example 1, a 50 μm thick glass cloth fabric was woven in a plain weave using T-glass yarn (IPC name: D450) specified in JIS R3413 in the same manner as in Application Example 1, and a toluene solution of the bismaleimide resin of Application Example 1 was impregnated with the bismaleimide resin. Soaking The glass cloth prepreg was laminated in three layers and heat-cured in a press at 200°C for 30 minutes to obtain a three-layer carbon nanotube nonwoven fabric composite sheet. The transmission loss in the machine direction and the cross direction was measured using this sheet. In addition, test pieces were cut out from the machine direction and the cross direction of the nonwoven fabric sheet to measure the tensile strength. The measurement results are shown in Table 5.
[0070] [Table 5] [Explanation of symbols]
[0071] 1. Measurement sample 2 Antennas 3 Incident wave 4 Transmitted wave
Claims
1. For 100 parts by mass of water, Basic compound: 0.001 parts by mass or more, 0.001 parts by mass or more of a cholic acid derivative, and Carbon nanotubes: 0.01 to 10.0 parts by mass The carbon nanotube aqueous dispersion contains the cholic acid derivative in an amount of 0.1 to 5.0 (parts by mass / parts by mass) relative to the carbon nanotubes.
2. 2. The carbon nanotube aqueous dispersion according to claim 1, wherein the cholic acid derivative is at least one selected from the group consisting of α-muricholic acid, β-muricholic acid, cholic acid, deoxycholic acid, ursodeoxycholic acid, hyodeoxycholic acid, chenodeoxycholic acid, dehydrocholic acid, and lithocholic acid.
3. The carbon nanotube aqueous dispersion according to claim 1 , wherein the basic compound is a nitrogen-containing compound.
4. The carbon nanotube aqueous dispersion according to claim 3 , wherein the nitrogen-containing compound is ammonia.
5. The carbon nanotube aqueous dispersion was measured at a shear rate of 100 s at 25° C. using a cone-plate type rotational viscometer according to JIS K7117-2:1999. -1 Viscosity (η100) and shear rate at 0.1 s -1 2. The carbon nanotube aqueous dispersion according to claim 1, wherein the thixotropy ratio, which is the ratio (η0.1 / η100) of the viscosity at η0.1 to the viscosity at η0.1, is from 50 to 1,000.
6. A step of preparing an aqueous dispersion solution containing 100 parts by mass of water, 0.001 parts by mass or more of a basic compound, and 0.001 parts by mass or more of a cholic acid derivative. and A step of dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass). The present invention relates to a method for producing an aqueous dispersion of carbon nanotubes.
7. (1) adding and mixing 0.001 parts by mass or more of a basic compound into 100 parts by mass of water to prepare a basic aqueous solution having a pH of 8 to 12; (2) dissolving 0.001 parts by mass or more of a cholic acid derivative in the basic aqueous solution to prepare an aqueous solution for dispersion; and (3) dispersing carbon nanotubes in the aqueous dispersion solution in an amount of 0.01 to 10.0 parts by mass and an amount of cholic acid derivative added relative to the carbon nanotubes in an amount of 0.1 to 5.0 (parts by mass / parts by mass); The present invention relates to a method for producing an aqueous dispersion of carbon nanotubes.
8. (4) A step of applying the carbon nanotube aqueous dispersion according to any one of claims 1 to 5 on a support to a thickness of 5 mm or less, and removing water in a drying furnace to produce a carbon nanotube thin film; and (5) peeling the carbon nanotube thin film obtained in step (4) from the support; At atmospheric pressure, at temperatures between 250°C and 500°C or At a pressure less than atmospheric pressure and at a temperature between 150°C and 500°C Heat treatment process A method for producing a carbon nanotube nonwoven fabric comprising the steps of: A method for producing a carbon nanotube nonwoven fabric, wherein the content of a cholic acid derivative in the carbon nanotube nonwoven fabric is 0 mass % or more and less than 10 mass %.
9. The method for producing a carbon nanotube nonwoven fabric according to claim 8, wherein the heat treatment is carried out in an inert gas.
10. A carbon nanotube nonwoven fabric having a sodium atom content of 1.0 mass % or less.
11. 11. The carbon nanotube nonwoven fabric according to claim 10, wherein the ratio of tensile strength in the longitudinal direction to the transverse direction (tensile strength in the longitudinal direction / tensile strength in the transverse direction) is 0.95 to 1.05.
Citation Information
Patent Citations
Method for producing organic nanotubes, especially lithocholic acid nanotubes, and uses thereof
JP2005507320A
Carbon nanotube aqueous dispersion
JP2009242126A
Organized assembly of carbon and non-carbon, and method of making same
JP2009535294A
Synthetic fiber, synthetic fiber yarn or fiber structure having carbon NANO tubes adhered thereto and method for producing these
JP2010261108A
CNT isolated dispersion
JP2012144388A